Conflict Resolution Between Security Guard and Security Service Provider (Case Study : PT Cakra Mandiri Perkasa Depok) - Mohammad NASIKHIN; Kholil KHOLIL; Mirza RONDA; Titiwidaningsih TITIWIDANINGSIH (International Journal of Environmental, Sustainability, and Social Science, 2023)
Based on The main cause of internal conflict in a security service provider company, which is usually caused by the problem of conflicting expectations, namely dissatisfaction with compensation for wages, overtime and Jamsostek that are not in line with the expectations of security members, finally found several other causes of conflict. The right solution is of course very much needed to provide satisfaction to all security members. By identifying the factors that play a role in the dimensions of internal conflict resolution between personal security and security service providers, related to organizational communication, it is hoped that a conflict resolution model can be built in companies that are experiencing internal conflicts based on organizational communication. Methodand research design using qualitative research with a case study design (case study). This research case study is related to the problem of internal conflict between workers (security personnel) and security service providers. The key informants in this research are Security Members, Security Service Provider Employees and several other supporting informants. It turns out that the problem of conflict of expectations is the most dominant factor in the occurrence of conflict so that conflict resolution related to the dissatisfaction that causes the conflict is to build a conflict resolution model.